PENGARUH CITRA MEREK, KUALITAS PRODUK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN (STUDI PADA PELANGGAN MUSTIKA RATU DI FISIP UNDIP) - P, Purwantini; Nurseto, Sendhang (Jurnal Ilmu Administrasi Bisnis, 2019)
The purpose of study is to determine the effect of brand image, product quality and customer satisfaction on customer loyalty Mustika Ratu. This type of research is explanatory research. The sampling technique uses non probability sampling techniques with purposive sampling method. The number of samples taken were 97 respondents from Mustika Ratu customers at the UNDIP FISIP. The results showed that brand image had an effect on customer loyalty by contributing 57.9% while the rest was influenced by factors other than brand image. Product quality has an effect on customer loyalty by contributing 78.7% while the rest is influenced by factors other than product quality. Customer satisfaction has an effect on customer loyalty by contributing 78.6% while the rest is influenced by other factors besides customer satisfaction. While the influence of brand image, product quality and customer satisfaction together affect customer loyalty by 52.8% while the remaining 47.2% is a contribution from other factors. Based on the calculation of the F test shows that there is a positive influence between brand image, product quality and customer satisfaction. This means that the better the brand image, product quality and customer satisfaction, the higher the level of customer loyalty Mustika Ratu. Based on the results of the study, the author can give advice to PT Mustika Ratu to maintain a natural and traditional image that has been adhering to the brand and continues to improve product quality both in terms of packaging and raw materials to be able to meet customer expectations.